Business processes and information technology - Ulric J.Gelinas; Steve G Sutton; Jane Fedorowicz (Thomson South-Western, 2004)
This text prepares students to effectively use, manage, and participate in the development of information technology applications in support of common business processes. Interconnections among an organization's management, business processes, information systems and information technology are brought out in each chapter. Another emphasis throughout the text is the governance, control, and security of business processes, information systems--especially underlying financial information systems--and emerging technologies. Moreover, the text centers around three themes: IT innovations, e-business and enterprise systems.